PREDIKSI CURAH HUJAN DI KOTA MAUMERE TAHUN 2022DENGAN METODE SARIMA - Debora Oktaviana Lado; Octavianus Jori; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2022)
Indonesia is a tropical country that consists of 2 seasons. However, the change of seasons in Indonesia is currently unpredictable. The same thing happened in Maumere City. Instabilities in weather and climate that affect the seasons prevent rainfall intensity from being estimated by analogy. Meanwhile, rainfall information is needed in various fields. Therefore, rainfall prediction research was carried out using the Seasonal Autoregressive Integrated Moving Average (SARIMA) method. Rainfall prediction is done by analyzing rainfall data in Maumere City every month from 2014 to 2021 which is taken from the Meteorology, Climatology and Geophysics Agency (BMKG) of the Maumere Climatology Station. The results obtained are the best SARIMA model, namely the SARIMA model (1,1,1) (0,1,1)23 . From the best model, the results of the prediction of the City of Maumere in 2022 are obtained, namely the maximum rainfall occurs in November with a total rainfall of 214 mm. While the minimum rainfall occurs in May with a total rainfall of 22 mm. The average rainfall in 2022 is 93.17 mm.